DEVELOPMENT OF WORDWALL EDUCATIONAL GAME-BASED EVALUATION INSTRUMENTS IN MATHEMATICS SUBJECTS IN CLASS IV SDN LALADON 02 BOGOR REGENCY FY 20232024 - Fadillah, Farid; Arief, Zainal Abidin; Raini, Yeni (Educational Researcher Journal, 2024)
The learning process has been transformed into a form of learning that uses technology, especially the internet. With advances in technological tools in the education sector, researchers are developing existing evaluation tools by utilizing websites Wordwall. The results of the needs questionnaire show that teachers have not used evaluation tools to determine student grades. In the assessment process, teachers still apply traditional methods such as paper exams. Therefore, there is a need for evaluation tools that can expand students' ways of thinking when learning. The aim of this research is to determine the feasibility of an educational game-based evaluation instrument Wordwall in Mathematics subjects in class IV SDN Laladon 02 Bogor Regency. This research method uses R&D using the Borg and Gall model using the Borg and Gall model development procedure adapted by Sugiyono, however this research only uses 8 stages out of 10 research stages because it is limited by researchers according to research needs and ongoing developments. The subjects of this research were fourth grade students at SDN Laladon 02, Bogor Regency. This research creates an educational game-based evaluation tool Wordwall using interview, observation and questionnaire data collection methods. The data analysis technique used is product feasibility testing. The research results showed that the feasibility test by media expert validation was 71% (feasible), language experts were 72% (feasible), learning design experts were 89.3% (very feasible), and material experts were 92% (very feasible). Furthermore, the results of individual trials were 81.6% (very feasible), and small group trials were 80.4 (feasible). The research results show that the evaluation tool is based on educational games Wordwall mathematics for class IV is considered suitable for use in the learning assessment process.